PEMANFAATAN MEDIA PEMBELAJARAN DALAM MENGEMBANGKAN INTERAKSI SOSIAL ANAK USIA DINI DI SLB AUTIS PONTIANAK - Ariani, Ully; Fadillah, Marmawi; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThis study aims to determine the Utilization of Learning Media in Developing Social Interaction in Early Childhood at Autism Extraordinary School in East Pontianak. The research method used in this study is a qualitative method with a case study approach. Data sources consist of 1 class teacher and 4 early children who experience autism disorder and data an observation sheet regarding the development of children's interactions and the results of interviews with classroom teachers and principals. The results of this study indicate that the type of learning media used at Autism Extraordinary School in East Pontianak are visual media and audiovisual media. The use of learning media is visual media in the form of picture cards and posters, while audiovisual media is in the form of films, videos and sound slides. The development of social interaction in children when using learning media is that children want to make eye contact, want to turn around when called and want to play with their friends. The advice given is that the type of learning media in enhancing social interaction in early childhood at Autism Extraordinary School in East Pontianak needs to be added, it is expected that the teacher can be more creative in using the media during the learning process, and it would be good at Kindergarten for Special Needs to also use lesson plan so that the learning process can well planned and implemented.Keywords: Learning Media, Social Interaction, Autistic Early Childhood.